Diffuse Tectonic Deformation in the Drum Mountains Fault Zone, Utah, USA: Testing the Utility of Legacy Aerial Photograph-Derived Topography - Stahl, Timothy A.; Niemi, Nathan A.; Delano, Jaime E.; Wolfe, Franklin D.; Bunds, Michael P.; Howell, Andrew (Frontiers in Earth Science, 2021)
The Basin and Range province in the western United States hosts numerous low-slip-rate normal faults with diffuse and subtle surface expressions. Legacy aerial photographs, widely available across the region, can be used to generate high-resolution digital elevation models of these previously uncharacterized fault systems. Here, we test the limits and utility of aerial photograph-derived elevation products on the Drum Mountains fault zone – a virtually unstudied and enigmatic fault system in the eastern Basin and Range province of central Utah. We evaluate a new 2-m digital surface model produced from aerial photographs against other remotely sensed and field survey data and assess the various factors that contribute to noise, artefacts, and distortions. Despite some challenges, the new elevation model captures the complex array of cross-cutting fault scarps well. We demonstrate that the fault zone has variable net east- or west-down sense of displacement across a c. 8-km-wide zone of antithetic and synthetic traces. Optically stimulated luminescence ages and scarp profiles are used to constrain net extension rates across two transects and reveal that the Drum Mountains fault zone has average extension rates of c. 0.1 to 0.4 mm yr-1 over the last c. 35 ka. These rates are both faster than previously estimated and faster than most other faults in the region, and could be an order of magnitude higher if steep faults at the surface sole into a detachment at depth. Several models have been proposed for local and regional faulting at depth, but our data show that the offsets, rates, and geometries of faulting can be generated by the reactivation of pre-existing, cross-cutting faults in a structurally complex zone between other fault systems. This study highlights how legacy aerial-photograph-derived elevation products, in lieu of other high-resolution topographic datasets, can be used to study active faults, especially in remote regions where diffuse deformation would otherwise remain undetected.